Differential Activity of the Oral Glucan Synthase Inhibitor SCY-078 against Wild-Type and Echinocandin-Resistant Strains of Candida Species - Pfaller, Michael A. (Antimicrob Agents Chemother, 2017)
SCY-078 (formerly MK-3118) is a novel orally active inhibitor of fungal β-(1,3)-glucan synthase (GS). SCY-078 is a derivative of enfumafungin and is structurally distinct from the echinocandin class of antifungal agents. We evaluated the in vitro activity of this compound against wild-type (WT) and echinocandin-resistant isolates containing mutations in the FKS genes of Candida spp. Against 36 Candida spp. FKS mutants tested, 30 (83.3%) were non-WT to 1 or more echinocandins, and only 9 (25.0%) were non-WT (MIC, >WT-upper limit) to SCY-078. Among C. glabrata isolates carrying FKS alterations, 84.0% were non-WT to the echinocandins versus only 24.0% for SCY-078. In contrast to the echinocandin comparators, the activity of SCY-078 was minimally affected by the presence of FKS mutations, suggesting that this agent is useful in the treatment of Candida infections due to echinocandin-resistant strains.